Coronary artery bypass graft surgery on a beating heart / Mohd Zamrin Dimon - Dimon, Mohd Zamrin (UiTM Press, 2024)
Coronary artery disease (CAD) continues to remain a major global health issue, standing as the leading cause of morbidity (disease) and mortality (death) since 800 BCE. Homer's Odyssey once described a significant number of deaths due to CAD demonstrated by sudden, nontraumatic death (John, 2012). Even in today's modern world, this condition remains the leading cause of death in both developed and developing countries, which is influenced by environmental factors, lifestyle, and genetic background (Malakar et al., 2019).